A sociological approach of literature in Leo N. Tolstoy’s short story God Sees the Truth, But Waits - Peni Larasati; Noer Doddy Irmawati (EduLite: Journal of English Education, Literature and Culture, 2022)
Sociology is defined as the social life, change, and the causes and consequences of human behavior study. Literature means any written work, and it can refer to a single work itself or a categorical understanding of literature. Furthermore, the sociology of literature is a specialized area of study which focuses its attention upon the relationship between a literary work and the social structure in which it is created. The objective of this study is to find out and to describe the elements of a sociology of literature in a short story entitled God Sees the Truth, But Waits by Leo N. Tolstoy. Technically, this study talked about the relation between literature and sociology. This study used sociological methods by describing the characteristics and the facts related to people and particular areas. It explained some aspects like introduction, discussion and description, and closure. The present researchers found sociological aspects such as social facts, social history, social behavior and event, and also literature aspects like jobs, residence, customs, and romance in the discussion and description section in the short story which also as the real-life reflection.